Campur Kode Pemelajar Bahasa Indonesia di Universitas Thammasat Thailand - Hari Bakti Mardikantoro; Rahayu Pristiwati; Wati Istanti; Hamam Supriyadi (Indonesian Language Education and Literature, 2024)
Penelitian ini bertujuan menentukan wujud campur kode serta faktor yang mempengaruhi wujud campur kode pada peristiwa tutur pemelajar bahasa Indonesia bagi penutur asing di Universitas Thammasat Thailand. Untuk mengkaji masalah dalam penelitian ini digunakan pendekatan kualitatif dengan teori sosiolinguistik. Data dijaring dengan menggunakan metode simak dan metode cakap. Adapun peristiwa tutur yang diteliti adalah peristiwa tutur para pemelajar bahasa Indonesia di Universitas Thammasat Thailand. Untuk menganalisis data digunakan metode padan subjenis referensial. Selain itu, analisis data juga menggunakan model Miles dan Huberman. Hasil penelitian adalah ada campur kode pada tuturan mahasiswa Universitas Thammasat yang sedang belajar bahasa Indonesia melalui Program BIPA. Jenis campur kode tersebut adalah campur kode ekstern karena campur kode terjadi antara bahasa Indonesia dan bahasa asing (bahasa Thai). Adapun faktor yang memengaruhi terjadinya campur kode adalah penutur dan topik pembicaraan. Hasil penelitian ini diharapkan dapat dimanfaatkan sebagai bahan ajar mata kuliah BIPA dan sosiolinguistik.Code Mixing in Indonesian Language Learners' Speech Events for Foreign Speakers at Thammasat University, ThailandThis research aims to determine the form of code mixing and the factors that influence the form of code-mixing in the speech events of Indonesian language learners for foreign speakers at Thammasat University, Thailand.Â  A qualitative approach was used to examine the problem in this research, using sociolinguistic theory. Data was collected using the listening method and the skill method. The speech events studied were those of Indonesian language students at Thammasat University, Thailand. The referential subtype matching method was used to analyze the data. Apart from that, data analysis also uses the Miles and Huberman model. The results of the research show that there is code-mixing in the speech of Thammasat University students who are studying Indonesian through the BIPA Program. This type of code-mixing is external code mixing because code mixing occurs between Indonesian and a foreign language (Thai). The factors that influence the occurrence of code-mixing are the speaker and the topic of conversation. It is hoped that the results of this research can be used as teaching material for BIPA and Sociolinguistics.